BrTTG1 regulates seed coat proanthocyanidin formation through a direct interaction with structural gene promoters of flavonoid pathway and glutathione S-transferases in Brassica rapa L. - Zhao, Wenju; Li, Xiaojuan; Wen, Junqin; Li, Quanhui; Bian, Shuanling; Ren, Yanjing (Frontiers in Plant Science, 2024)
Introduction Seed coat color is a significant agronomic trait in horticultural crops such as Brassica rapa which is characterized by brown or yellow seed coat coloration. Previous Brassica rapa studies have shown that BrTTG1 is responsible for seed coat proanthocyanidin formation, which is dependent on the MYB-bHLH-WD40 complex, whereas some studies have reported that TRANSPARENT TESTA GLABRA 1 (TTG1) directly interacts with the structural gene promoters of the flavonoid pathway. Methods Herein, the brown-seeded inbred B147 and ttg1 yellow-seeded inbred B80 mutants were used as plant materials for gene expression level analysis, gene promoter clone and transient overexpression. Results The analysis identified eleven structural genes involved in the flavonoid biosynthesis pathway, which are potentially responsible for BrTTG1- dependent seed coat proanthocyanidin formation. The promoters of these genes were cloned and cis-acting elements were identified. Yeast one-hybrid and dual-luciferase assays confirmed that BrTTG1 directly and independently interacted with proCHS-Bra008792, proDFR-Bra027457, proTT12-Bra003361, proTT19-Bra008570, proTT19-Bra023602 and proAHA10-Bra016610. A TTG1-binding motif (RTWWGTRGM) was also identified. Overexpression of TTG1 in the yellow-seed B. rapa inbred induced proanthocyanidin accumulation by increasing the expression levels of related genes. Discussion Our study unveiled, for the first time, the direct interaction between TTG1 and the promoters of the flavonoid biosynthesis pathway structural genes and glutathione S-transferases in Brassica rapa. Additionally, we have identified a novel TTG1-binding motif, providing a basis for further exploration into the function of TTG1 and the accumulation of proanthocyanidins in seed coats.